Pemberdayaan Suami dalam Mendukung Kehamilan Sehat melalui Program Ayah Hebat di Desa Kubutambahan - Putu Monna Frisca Widiastini; Made Yos Kresnayana; Cindy Meilinda Sari; Indrie Lutfiana; Luh Ayu Purnami (Universitas Pahlawan Tuanku Tambusai, 2026)
Husbands' involvement plays an important role in supporting maternal and fetal health during pregnancy. This community service program aimed to improve husbands' knowledge and preparedness through the Ayah Hebat Program in Kubutambahan Village, Buleleng Regency. The intervention included health education, interactive discussions, simulation of pregnancy danger sign identification, and the development of a family birth preparedness plan. A total of 30 husbands of pregnant women participated in the program. Program effectiveness was evaluated using pre-test and post-test assessments and analyzed with the Wilcoxon Signed Rank Test because the data were not normally distributed. The results showed that the mean knowledge score increased from 61.3±10.4 before the intervention to 84.7±8.1 after the intervention, with a statistically significant difference (Z = −4.782; p = 0.003). Participants were also able to develop family birth preparedness plans, including health facility selection, transportation, blood donors, and healthcare provider contacts. The Ayah Hebat Program effectively improved husbands' knowledge and preparedness to support healthy pregnancies.